Time means… species! On the performance of species richness estimators and different sampling schemes. - Salgueiro, Pedro (2010)
Species richness is accounted as the oldest and the simplest concept of species diversity, being widely used in scientific grounds for monitoring and assessment purposes. However, the challenge is to correctly estimate the number of species. Not only estimates should be accurate, but also should be precise for correct assessment of a system’s state and trend. This study aims to determine differences between estimates derived from different sampling schemes and to evaluate the performance of observed richness and three non-parametric estimators frequently used (first-order Jackknife, second-order Jackknife and second-order Chao) by means of bias, inaccuracy and imprecision. In overall, our final goal is to establish recommendations for bird monitoring surveys and assessments.